2021
DOI: 10.1016/j.sjbs.2021.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of energy drink consumption and association with dietary habits among governmental university students in Riyadh

Abstract: To determine the prevalence of Energy Drinks (ED) consumption, and the adverse effects experienced by consumers among governmental university students in Riyadh, and to assess the relationship between ED consumption and dietary habits. This is a cross-sectional study carried out in 2020 in a random sample of students at government universities in Riyadh (King Saud University (KSU) and Imam Muhammad Ibn Saud Islamic University (IMSIU). The study was conducted within a time frame of 3 months which included a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
7
4
0
Order By: Relevance
“…We found that around 30.0% Saudi adults consume energy drinks on a weekly basis, which is in agreement with the most recent study performed among Saudi young adults (29.3%) ( 41 ). However, the results of the present study are inconsistent and lower compared with earlier studies executed in Saudi Arabia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that around 30.0% Saudi adults consume energy drinks on a weekly basis, which is in agreement with the most recent study performed among Saudi young adults (29.3%) ( 41 ). However, the results of the present study are inconsistent and lower compared with earlier studies executed in Saudi Arabia.…”
Section: Discussionsupporting
confidence: 92%
“…It could be also that females tend to more health-conscious and the desire to be a positive role-model. Previous research in several populations ( 34 , 41 , 47 , 48 ) has demonstrated a strong correlation between the age of an individual and their consumption of soft and energy drinks, and the current study’s findings support this. Our result was that young adults <29 y are more likely to consume soft and energy drinks compared to adults over the age of 50 y and those 30–49 y.…”
Section: Discussionsupporting
confidence: 85%
“…[13] A recent study in Riyadh examined the prevalence of energy drink consumption among students at King Saud University and Imam Muhammad bin Saud University reported that 36.88% of students began drinking energy drinks in middle school, with 53.6% citing delicious taste as their primary reason for doing so. [14] A variety of factors influence energy drinks consumption. According to some studies, excessive consumption of energy drinks is linked to a variety of factors, including peer pressure, smoking, a lack of knowledge about the ingredients, and living away from parents.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] A recent study in Riyadh examined the prevalence of energy drink consumption among students at King Saud University and Imam Muhammad bin Saud University reported that 36.88% of students began drinking energy drinks in middle school, with 53.6% citing delicious taste as their primary reason for doing so. [ 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of energy drink use varies widely, ranging from as low as 29.3% among students in government universities in Riyadh, Saudi Arabia 22 , to as high as 87% among medical and dental students in Nigeria 23 .…”
Section: Introductionmentioning
confidence: 99%